Impact of management practices on the income of transmigrant farmers in Wonosari, Gorontalo - Amelia Murtisari; Irham Irham; Agustinus Moonti; Rahmatiah Rahmatiah; Nurdin Nurdin; Pipit Sartika; Happy Amanda Delicia Rahmanto (Department of Agribusiness, Faculty of Agriculture, Universitas Trunojoyo Madura, Indonesi, 2024)
The transmigration program aims to improve welfare, mainly through wet rice farming. This research objectives are: 1) To analyze the management of wet rice farming in transmigration areas; 2) To analyze the income of wet rice farming in transmigration areas; and 3) To analyze the influence of management and other factors on the income of wet rice farmers in transmigration areas. A quantitative descriptive research method was employed, with sampling conducted through purposive sampling. The study identified two management models used by wet rice farmers. Model 1 employed the jajar legowo planting pattern, utilizing irrigation and labor from within and outside the family. Model 2 applied the tabela planting pattern, relying on both irrigation and borehole irrigation, and predominantly employs labor from outside the family. The average income of rice farmers in Model 1 was IDR 3,278,446.21 per planting cycle, while in Model 2, it was IDR 1,797,150.33. Factors affecting the household income of transmigrant wet-rice farmers include age, education, land area, and farm management model.